Caffeine protects against disruptions of the blood-brain barrier in animal models of Alzheimer’s and Parkinson’s disease - Chen, Xuesong (2010)
Sporadic Alzheimer’s disease (AD) and Parkinson’s disease (PD) are two of the most common neurodegenerative diseases and as such they represent major public health problems. Finding effective treatments for AD and PD represents an unmet and elusive goal largely because these diseases are chronic and progressive, and have a complicated and ill-understood pathogenesis. Although the underlying mechanisms are not fully understood, caffeine, the most commonly ingested psychoactive drug in the world, has been shown in human and animal studies to be protective against AD and PD. One mechanism implicated in the pathogenesis of AD and PD is blood-brain barrier (BBB) dysfunction and we reported recently that caffeine exerts protective effects against AD and PD at least in part by keeping the BBB intact. The present review focuses on the role of BBB dysfunction in the pathogenesis of AD and PD, caffeine’s protective effects against AD and PD, and potential mechanisms whereby caffeine protects against BBB leakage.